Quality adjustment of European price statistics and the role for hedonics - Henning Ahnert; Geoff Kenny (European Central Bank (ECB), 2004)
In this paper we review the well-known problem of how to measure price developments when the quality of the underlying goods and services is changing over time. The importance of appropriate methods to take account of quality change is highlighted from the perspective of monetary policy. In particular, we highlight the need for credible and transparent price indicators. In this context, we review the hedonic approach to calculating quality-adjusted price indices and assess the available information on their effects as well as their potential for improving credibility and comparability. Current practices as regards quality adjustment in the European Union (EU) are also discussed, with particular emphasis on the Harmonised Index of Consumer Prices (HICP). Overall, we give a qualified endorsement of hedonics for specific product categories and make some suggestions about how the work on quality adjustment in the EU can be further developed, focusing in particular on the role of hedonics.
Keywords: 330; Preisstatistik; Statistische Methode; Anpassung; Hedonischer Preisindex; EU-Staaten